A novel CeO2/InVO4 composite with high visible-light induced photocatalytic activity - Jindaporn Chaisorn (2018)
© 2015 Elsevier B.V. All rights reserved. A novel visible light-driven CeO < inf > 2 < /inf > /InVO < inf > 4 < /inf > composite photocatalyst was successfully synthesized by coupling of hydrothermal method and homogeneous precipitation method. The photocatalysts were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) UV-vis diffuse reflectance spectroscopy, and photoluminescence techniques. The synthesized CeO < inf > 2 < /inf > /InVO < inf > 4 < /inf > composite was used as the efficient photocatalysts for the photocatalytic degradation of methylene blue (MB) under visible light illumination which shows the degradation (72%) of MB in 120 min. The enhanced photocatalytic performance of CeO < inf > 2 < /inf > /InVO < inf > 4 < /inf > arises from more sufficient interfacial interaction between CeO < inf > 2 < /inf > and InVO < inf > 4 < /inf > , leading to extended photoresponding range, enhanced photogenerated charge separation, and transportation efficiency.